Legality Of Land Certificate Issued By Village Head As The Basis For Land Sale And Purchase Transaction - Bima Bagaskara, Arga Nanda (Universitas Islam Malang, 2023)
Abstract : The village head is the highest stakeholder in the village community where the authority to decide a community problem is in the hands of the village head. One of these authorities is to resolve land allergy problems arising from disputes, overlapping ownership or other problems arising from misunderstandings The community in understanding the land problem. This research has 2 (two) problem formulations, namely (1) Can the deed under hand be used as the basis for issuing a certificate? (2) What is the basis for a land certificate to have legal force for the landowner? The type of research used in this study is normative research , this research uses a statutory approach (statute approach) and a comparative approach approach (comparative approach). The results of this study are the legal basis for the authority of the village head in issuing land certificates and fungsi land certificates as evidence of guidance legal ownership of land.Keywords: village head, land certificate, land issue.